Comparison of signaling interactions determining annual and perennial plant growth in response to low temperature - Wingler, Astrid (Frontiers in Plant Science, 2015)
Low temperature inhibits plant growth despite the fact that considerable rates of photosynthetic activity can be maintained. Instead of lower rates of photosynthesis, active inhibition of cell division and expansion is primarily responsible for reduced growth. This results in sink limitation and enables plants to accumulate carbohydrates that act as compatible solutes or are stored throughout the winter to enable re-growth in spring. Regulation of growth in response to temperature therefore requires coordination with carbon metabolism, e.g. via the signaling metabolite trehalose-6-phosphate. The phytohormones gibberellins (GA) and jasmonate (JA) play an important role in regulating growth in response to temperature. Growth restriction at low temperature is mainly mediated by DELLA proteins, whose degradation is promoted by GA. For annual plants, it has been shown that the GA/DELLA pathway interacts with JA signaling and C-repeat binding factor (CBF) dependent cold acclimation, but these interactions have not been explored in detail for perennials. Growth regulation in response to seasonal factors is, however, particularly important in perennials, especially at high latitudes. In autumn, growth cessation in trees is caused by shortening of the daylength in interaction with phytohormone signaling. In perennial grasses seasonal differences in the sensitivity to GA may enable enhanced growth in spring. This review provides an overview of the signaling interactions that determine plant growth at low temperature and highlights gaps in our knowledge, especially concerning the seasonality of signaling responses in perennial plants.